2010
DOI: 10.1039/b918845b
|View full text |Cite
|
Sign up to set email alerts
|

Nanocapsules with “invisible” walls

Abstract: Nanometre-thin membranes, prepared by directed assembly within lipid bilayers, are capable of unhindered transport of ions while being impermeable to medium sized molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 19 publications
(6 reference statements)
3
92
0
Order By: Relevance
“…Aqueous dispersions of nanocapsules are stabilized by sodium dodecyl sulfate (SDS). Transmission and scanning electron microscopy (TEM and SEM) images showed spherical structures (Figure c, d, e) similar to previously reported liposome‐ and surfactant‐templated nanocapsules ,,. GNPs were well‐distributed in hollow nanocapsules.…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…Aqueous dispersions of nanocapsules are stabilized by sodium dodecyl sulfate (SDS). Transmission and scanning electron microscopy (TEM and SEM) images showed spherical structures (Figure c, d, e) similar to previously reported liposome‐ and surfactant‐templated nanocapsules ,,. GNPs were well‐distributed in hollow nanocapsules.…”
Section: Figuresupporting
confidence: 86%
“…The nanocapsules used here are prepared by directed assembly using bilayers of surfactant vesicles as templates . We have recently shown that polymer nanocapsules with nanometer‐thin walls revealed unusual properties, for example, ultra‐fast transport of ions while ensuring the long‐term retention of molecules larger than pores . Due to the small thickness of the walls, these hollow capsules have high payload capacity.…”
Section: Figurementioning
confidence: 99%
“…To address these conflicting requirements the indicator dyes can be encapsulated into porous nanocapsules [37]. The~0.8 nm thin walls of the nanocapsules do not slow the mass transport of hydronium ions [38] but the nanocapsules themselves have almost no mobility inside of a gel, i.e., no leaching of the dye and no drift in the sensor signal is expected.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insights into the kinetics of transport through the shells of bilayertemplated NCs, the rates of protonation and deprotonation of encapsulated pH-sensitive dyes were investigated using stopped flow technique coupled with absorbance and fluorescence spectroscopy [56]. In these experiments, an aqueous suspension of surfactant-stabilized NCs containing pyranine or bromophenol blue was rapidly mixed with a base or an acid followed by measuring fluorescence increase for the deprotonated form of pyranine or absorbance decrease for the protonated form of bromophenol blue.…”
Section: Synthesis and Characterization Of Nanocapsulesmentioning
confidence: 99%